Fatigue-fracture characterization of wood under mode I loading - Dourado, N. (2019)
The objective of this work is to study wood fatigue behaviour under mode I loading. The double cantilever beam test was used to perform fatigue tests in Pinus pinaster Ait. wood under several loading-levels. Fatigue lives and the coefficients of the modified Paris law were experimentally determined aiming at characterizing wood fatigue behaviour. A two-dimensional bilinear cohesive zone model appropriate for pure mode I fatigue loading was also used. The proposed formulation considers a single damage parameter englobing cumulative damage resulting from both static and fatigue loading. The experimental modified Paris law was used as an input in the model, which was subsequently applied to predict fatigue lives under different loading-levels. The good agreement obtained demonstrates the soundness of the proposed experimental procedure and the good performance of the numerical method as a predictive tool concerning wood fatigue-fracture characterization under pure mode I loading.